2009
DOI: 10.1002/jbm.a.32511
|View full text |Cite
|
Sign up to set email alerts
|

Electrical regulation of Schwann cells using conductive polypyrrole/chitosan polymers

Abstract: Electrical stimulation (ES) can dramatically enhance neurite outgrowth through conductive polymers and accelerate peripheral nerve regeneration in animal models of nerve injury. Therefore, conductive tissue engineering graft in combination with ES is a potential treatment for neural injuries. Conductive tissue engineering graft can be obtained by seeding Schwann cells on conductive scaffold. However, when ES is applied through the conductive scaffold, the impact of ES on Schwann cells has never been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 35 publications
3
133
0
Order By: Relevance
“…Collagen-PPy hybrid material prepared by the chemical polymerization of pyrrole, using FeCl 3 as initiator, was also carried out by these researchers in the presence of soluble collagen (Li and Khor, 1994). Huang et al (2010) fabricated a PPy-chitosan membrane, seeded Schwann cells on the scaffolds and showed that the PPy-chitosan membranes supported cell adhesion and proliferation, indicating its biocompatibility. We carried out the electrospinning of a blend of poly(ε-caprolactone) (PCL), gelatin and PANI to obtain conductive nanofibrous scaffolds for nerve tissue engineering.…”
Section: Modification Of Conductive Materials With Biopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen-PPy hybrid material prepared by the chemical polymerization of pyrrole, using FeCl 3 as initiator, was also carried out by these researchers in the presence of soluble collagen (Li and Khor, 1994). Huang et al (2010) fabricated a PPy-chitosan membrane, seeded Schwann cells on the scaffolds and showed that the PPy-chitosan membranes supported cell adhesion and proliferation, indicating its biocompatibility. We carried out the electrospinning of a blend of poly(ε-caprolactone) (PCL), gelatin and PANI to obtain conductive nanofibrous scaffolds for nerve tissue engineering.…”
Section: Modification Of Conductive Materials With Biopolymersmentioning
confidence: 99%
“…They concluded that electrical stimulation using clinically acceptable waveforms has a significant effect on the rate of release of both proteins (NT-3 and BDNF). Electrical stimulation has also been applied to Schwann cells cultured on polypyrrole-chitosan membrane (Huang et al, 2010). Constant potential gradient (100 mV/mm) was applied to the cells through the membrane for 4 h and then the cells were incubated for an additional 12, 24 or 36 h. The results showed that electrical stimulation applied through conductive PPy-chitosan significantly enhanced the viability of Schwann cells and dramatically enhanced secretion of NGF and brain-derived neurotrophic factor (BDNF) and protein expression.…”
Section: Application Of Electrical Stimulation In Nerve Tissue Enginementioning
confidence: 99%
“…These cells play a key role in nerve regeneration by secreting neurotrophic factors that help the axon sprouts grow towards the injured neurons 62 . Several reports demonstrated that the secretion/expression of both brainderived neurotrophic factor and neuron growth factor (NGF) were elevated on electrical stimulation [63][64][65] . Similar to the situation described above, our poly(EDOT-MI-co-EDOT-PC) films were inert towards the Schwann cells in the absence of attached ligands.…”
Section: Articlementioning
confidence: 99%
“…include transmitting electric impulses in neurite cultures, 12 regenerating nerves, 13 and healing wounds. 11 Cardiac applications to synchronize contractility in the injured myocardium have been suggested, but not functionally tested.…”
mentioning
confidence: 99%